Research, development and innovation in business enterprises: experience from Egypt - Motaz Khorshid; Mohamed Ramadan A. Rezk; Mohamed Ismail; Leonardo Piccinetti; Amr Radwan; Omneia Helmy; Mahmoud M. Sakr (Insights into Regional Development, 2023)
This paper addresses the linkages between research and development (R&D) and innovation on the one hand and the socioeconomic impact of research, development and innovation (RDI) on the other hand. More specifically, the paper suggests a two-stage methodology directed to analyse the performance of RDI in business enterprises and assess their development impact. A conceptual four-dimensional model and an integrated analytical framework were developed. This approach is complemented by the development of a statistical survey mainly designed to generate appropriate indicators for analysing the vital role of RDI in business enterprises. The survey results revealed several analytical points as well as specific imbalances of RDI system in business enterprises that need to be addressed by policymakers. Furthermore, the analytical results stress the need for Egyptian business enterprises to enhance and diversify their cooperation with other RDI-producing institutions to benefit from comparative advantages and improve the quality of RDI outputs.